The Green Revolution in India (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The Green Revolution in India was a significant period of agricultural transformation that took place in the 1960s and 1970s. This research paper aims to explore the various aspects of the Green Revolution in India, including its impact on agricultural productivity, food security, and socio-economic development. The paper will examine the key drivers of the Green Revolution in India, such as government policies, technological advancements, and international collaborations. It will also analyze the challenges and limitations of the Green Revolution, such as environmental degradation, inequality, and farmer distress. In conclusion, the Green Revolution in India was a transformative period in the country's agricultural history, which significantly increased crop yields and ensured food security for millions of people. However, the long-term sustainability of the Green Revolution is a subject of ongoing debate, as the environmental and social costs of intensive farming practices are becoming increasingly apparent. Moving forward, it is imperative for India to adopt sustainable agricultural practices that promote environmental conservation, preserve biodiversity, and ensure food security for future generations.